A Stormflow/Baseflow Comparison of Dissolved Organic Matter Concentrations and Bioavailability in an Appalachian Stream - Buffam, Ishi; Galloway, James N.; Blum, Linda K.; McGlathery, Karen J. (Biogeochemistry, 2001)
Patterns of dissolved organic carbon (DOC) and nitrogen (DON) delivery were compared between times of stormflow and baseflow in Paine Run, an Appalachian stream draining a 12.4 km2 forested catchment in the Shenandoah National Park (SNP), Virginia. The potential in-stream ecological impact of altered concentrations and/or chemical composition of DOM during storms also was examined, using standardized bacterial bioassays. DOC and DON concentrations in Paine Run were consistently low during baseflow and did not show a seasonal pattern. During storms however, mean DOC and DON concentrations approximately doubled, with maximum concentrations occurring on the rising limb of storm hydrographs. The rapid response of DOM concentration to changes in flow suggests a near-stream or in-stream source of DOM during storms. Stormflow (4% of the time, 36% of the annual discharge) contributed >50% of DOC, DON and NO3- flux in Paine Run during 1997. In laboratory bacterial bioassays, growth rate constants were higher on Paine Run stormflow water than on baseflow water, but the fraction of total DOM which was bioavailable was not significantly different. The fraction of the total stream DOC pool taken up by water column bacteria was estimated to increase from 0.03 ± 0.02% h-1 during baseflow, to 0.15 ± 0.04% h-1 during storms. This uptake rate would have a minimal effect on bulk DOM concentrations in Paine Run, but storms may still have considerable impact on the bacterial stream communities by mobilizing them into the water column and by supplying a pulse of DOM.